EDUKASI STRATEGI DIGITAL MARKETING DAN PENCATATAN FINANCIAL SEDERHANA DENGAN APLIKASI SMART PHONE UNTUK MENINGKATKAN PENJUALAN UMKM KERUPUK BAWANG DI DESA KEDALI LAMONGAN - Fatichatur Rachmaniyah; Siti Shoimah; Moh. Azus Shony Azar; Aldhian Nur Isnaini (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
This pandemic is increasingly hampering the development of Indonesian SMEs. The restrictions imposed have made the sales level of SMEs decrease significantly. Therefore, SMEs must be required to be creative in using digital application media to survive. So this is important for SMEs to know about digital marketing and how to record finances with smartphone applications to make the right financial decisions. The purpose of this dedication is to educate about the importance of digital marketing strategies to increase sales and manage finances with smartphone applications so that they can allocate funds more effectively. This activity was successful which resulted in the business of Kerupuk Bawang belonging to Mrs. Sholikhah already knowing how to optimize marketing with WhatsApp business features and knowing how to record finances well through the Money Manager application.